Who obtains abortion in Georgia and why? - Pestvenidze E; Stray-Pedersen B (Dove Medical Press, 2018)
Ekaterine Pestvenidze, Babill Stray-Pedersen Institute of Clinical Medicine, Rikshospitalet, Division of Women and Children, University of Oslo, Oslo, Norway Purpose: While induced abortion practices are common in Georgia, the sociodemographic subgroups of women predominantly affected by abortion and their leading motives have not yet been explored. The study aims to understand differentials in women undergoing abortion according to background characteristics and get insight into their reasons for availing of abortion services.Materials and methods: We analyzed the data on 2,054 abortions from the Georgian Reproductive Health Survey 2010. We computed an abortion index (AI) to identify the subgroups of women with the highest relative abortion rates. We performed descriptive analysis of the reasons for pregnancy termination and assessed the statistical significance of differences in proportions using the chi-squared test. We applied multivariate binary logistic regression analyses to study the sociodemographic predictors of the four leading reasons for abortion.Results: In Georgia, women seeking abortion were predominantly those with two or more children (AI 1.9–2.2), from an Azeri ethnic group (AI 2.0), in the age category 25–34 years (AI 1.5), married (AI 1.5), or practicing Islam (AI 1.5). Unwillingness to have more children was the most commonly cited reason for the abortion decision (49.4%), followed by socioeconomic concerns (22.0%) and desire to space out pregnancies (18.1%). Health-related reasons were cited by only 7.5% as a leading motive for abortion.Conclusion: Women with specific background characteristics are disproportionally affected by abortion and, thus, are in utmost need of support in successful birth planning. Desire to stop or space childbearing and socioeconomic challenges are the overriding motives for terminating unintended pregnancies. Planning and execution of effective family planning programs targeting those at greatest risk for abortion have the potential to reduce the burden of induced abortion in Georgia. Keywords: induced abortion reason, Georgia, family planning